Rural development. - World Bank. ([Washington] : World Bank, 1975)
The book is on the strategy designed to improve the economic and social life of a specific group of people - the rural poor. It involves extending the benefit of development to the poorest among those who seek a livelihood in the rural areas.
Cover title.
Includes bibliographical references.
gp. 24/ 01/ 2019
Loan
Keywords: Rural development; Rural conditions; Economic assistance